Multilayer assembly of hyaluronic acid/poly(allylamine) control of the buildup for the production of hollow capsules - Szarpak, Anna (Langmuir : the ACS journal of surfaces and colloids, 2008)
The objective of this work was to investigate the formation of hollow microcapsules composed of hyaluronic acid (HA) and poly(allylamine) (PAH) by layer-by-layer adsorption on CaCO 3 microparticles and subsequent core removal by addition of chelating agents for calcium ions. We found that the molecular weight of HA as well as the HA solution concentration used during deposition are crucial parameters influencing the multilayer structure. Whereas the effect of molecular weight of HA was mainly attributed to the porous structure of the template which allows penetration of polyelectrolytes when their size is below the maximum pore size of the template ( approximately 60 nm), that of the concentration of the HA solution was related to the intrinsic properties of the polysaccharide. Indeed, as shown by quartz crystal microbalance with dissipation monitoring as well as electron microscopy techniques, the latter leads to dense structures for concentrations from five to ten times the critical overlap concentration during adsorption. Such conditions were found to be favorable for the formation of hollow shells. Regarding conditions for core dissolution, we demonstrated the possibility to use either ethylenediaminetetraacetic acid (EDTA) or citric acid as chelating agents. However, in some cases, it was necessary to chemically cross-link the shell to maintain its integrity